Nano-diamond / graphene composite material loaded platinum-ruthenium bimetallic catalyst and preparation and application thereof

The platinum-ruthenium bimetallic catalyst supported by nanodiamond/graphene composite material solves the problems of insufficient activity and high cost of traditional catalysts at low temperatures, and achieves efficient and stable carbon monoxide oxidation reaction, reducing costs and improving utilization.

CN119259037APending Publication Date: 2025-01-07INST OF METAL RESEARCH - CHINESE ACAD OF SCI
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202411549664.3
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-11-01
Publication Date
2025-01-07

AI Technical Summary

Technical Problem

Traditional carbon monoxide oxidation catalysts have poor catalytic activity at low temperatures, and precious metal catalysts have high cost and low utilization, making it difficult to meet the demand for efficient carbon monoxide removal.

Method used

The platinum-ruthenium bimetallic catalyst supported by nanodiamond/graphene composite material was uniformly supported by the co-impregnation method, and pretreated using a mixed gas of hydrogen, oxygen, helium and carbon monoxide to optimize the catalyst interface site.

Benefits of technology

It realizes efficient conversion of carbon monoxide at low temperatures, maintains stable catalytic performance for a long time, reduces catalyst costs, and improves raw material utilization.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure HDA0005114728140000011
    Figure HDA0005114728140000011
  • Figure HDA0005114728140000012
    Figure HDA0005114728140000012
  • Figure HDA0005114728140000013
    Figure HDA0005114728140000013
Patent Text Reader

Abstract

The invention discloses a nano-diamond / graphene composite material loaded platinum-ruthenium bimetallic catalyst as well as preparation and application thereof, and belongs to the technical field of CO oxidation catalysts. According to the catalyst, a nano diamond / graphene composite material of a core-shell structure serves as a carrier, precious metal Pt serves as an active component, Ru serves as an auxiliary, a metal salt solution containing platinum and ruthenium serves as a precursor, Pt-Ru is bonded with carbon atoms with graphene defects on the surface of the carrier in a diatom pair mode through a co-impregnation method, and the catalyst is obtained. And loading to the surface of the composite material. The method provided by the invention is high in raw material utilization rate, relatively low in cost, simple in preparation process and easy to popularize and apply, and the prepared catalyst shows excellent catalytic performance in CO oxidation reaction, can realize high CO conversion rate at low temperature and can keep stable performance for a long time.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention belongs to the technical field of CO oxidation catalysts, and particularly relates to a platinum-ruthenium bimetallic catalyst supported on a nanodiamond / graphene composite material, and the preparation and application thereof. Background Art

[0002] CO, as a colorless and odorless toxic gas, can cause serious harm to the environment and human life and health. CO is mainly produced by the incomplete combustion of fossil fuels, including boiler exhaust, automobile exhaust, etc. Especially for closed or semi-closed residential living environments, exploring efficient methods to eliminate CO is imperative for human safety and environmental protection. In addition, hydrocarbon reforming reactions in the industrial hydrogen production process also produce a small amount of CO, which poses great difficulties for the further purification and utilization of energy. Today, the most direct, economical and effective method for removing CO is catalytic oxidation, which is currently widely used in related fields such as air purification and automobile exhaust treatment. The CO catalytic oxidation method utilizes the high catalytic activity of the catalyst to oxidize CO to CO2, and its core lies in the design of an efficient catalyst. The traditional carbon monoxide oxidation catalyst is a supported precious metal Pt-based catalyst. However, pure Pt nanoparticle catalysts will poison their metal sites due to the strong adsorption of CO at low temperatures, hindering the occurrence of CO oxidation catalytic reactions, resulting in poor CO oxidation activity at low temperatures. In addition, due to the small reserves, low output and high prices of precious metals, there is an urgent need to design low-cost, high-utilization efficient CO oxidation catalysts to meet the current urgent needs.

[0003] The physicochemical properties of the support and dopant, as well as the atomic utilization of active sites and the reaction atmosphere, are important factors influencing the catalytic activity of Pt-based catalysts. Research has found that the introduction of a second component can improve the adsorption of reactants and products onto the metal sites, preventing CO poisoning and promoting the adsorption and activation of O2, thereby enhancing the low-temperature CO oxidation performance of Pt-group catalysts. This paper designs a novel carbon-supported Pt / Ru diatomic catalyst that maximizes atomic utilization and exhibits excellent activity in low-temperature CO oxidation reactions. Summary of the Invention

[0004] To overcome the shortcomings of the existing technology, the present invention aims to provide a nanodiamond / graphene composite-supported platinum-ruthenium bimetallic catalyst, its preparation method, and its application. When used for CO catalytic oxidation, the prepared catalyst can achieve efficient CO conversion at low temperatures and maintain stable performance over a long period of time.

[0005] To achieve the above object, the technical solutions adopted by the present invention are as follows:

[0006] A nano-diamond / graphene composite material-supported platinum-ruthenium bimetallic catalyst is disclosed. The catalyst uses the nano-diamond / graphene composite material as a carrier, and Pt-Ru elements are uniformly supported on a graphene layer on the surface of the nano-diamond / graphene composite material carrier in the form of atomic pairs. The noble metal Pt is an active component with a mass percentage of 0.1wt%-0.2wt%; Ru is an auxiliary agent with a mass percentage of 0.05wt%-0.1wt%. The catalyst is used for CO catalytic oxidation reaction.

[0007] The carrier is a core-shell structure material formed by taking nano-diamond as a core and graphene rich in surface defects as a shell.

[0008] The preparation method of the nanodiamond / graphene composite material supported platinum-ruthenium bimetallic catalyst comprises the following steps:

[0009] (1) calcining the nanodiamond powder at high temperature and then cooling it naturally to synthesize a nanodiamond / graphene composite material for use as a carrier;

[0010] (2) adding chloroplatinic acid and ruthenium chloride solutions in appropriate proportions to anhydrous ethanol and mixing them uniformly to obtain a metal salt solution, loading platinum and ruthenium on a nanodiamond / graphene composite material carrier by a co-impregnation method to obtain a nanodiamond / graphene composite material-loaded platinum-ruthenium catalyst precursor, and vacuum drying the mixture for 12 h to 24 h;

[0011] (3) placing the prepared solid precursor in a quartz tube and pre-treating it in a mixed atmosphere of hydrogen, oxygen, carbon monoxide and helium to obtain the nanodiamond / graphene composite material loaded with platinum-ruthenium bimetallic catalyst.

[0012] In the above step (1), the preparation process of the nano-diamond / graphene composite material loaded with platinum-ruthenium bimetallic catalyst is as follows: nano-diamond powder is calcined at high temperature, and the nano-diamond / graphene composite material is obtained after high-temperature surface graphitization; wherein, the high-temperature calcination treatment conditions are: the nano-diamond powder raw material is placed in a high-temperature furnace, and calcined at 900°C-1100°C for 3h-5h under an inert gas atmosphere (80mL / min-100mL / min), and the nano-diamond / graphene composite material is obtained after natural cooling.

[0013] The co-impregnation method comprises the following steps: adding a 20 mg / mL chloroplatinic acid solution and a ruthenium chloride solution to anhydrous ethanol according to the loading ratio, controlling the molar ratio of platinum to ruthenium to be 1:1; adding the nanodiamond / graphene composite material thereto, uniformly dispersing the solution by ultrasonication, and then stirring the solution with a magnetic stirrer in an open environment. After the ethanol is completely evaporated, the solution is dried in a vacuum environment and naturally cooled to room temperature to obtain a platinum-ruthenium bimetallic catalyst precursor supported on the nanodiamond / graphene composite material; wherein the ratio of the nanodiamond / graphene composite material added to the anhydrous ethanol is 200:(2-5) mg / mL;

[0014] During the co-impregnation method, the ultrasonic time is 10 min-30 min, the magnetic stirring time is 12 h-24 h, the drying temperature is 60° C., and the drying time is 12 h-24 h.

[0015] In the above step (3), during the pretreatment process, the volume ratio of H2 in the mixed atmosphere is 48%, the volume ratio of CO is 1%, the volume ratio of O2 is 1%, and the balance is He. The pretreatment temperature is 300°C, the mixed gas flow rate is 20mL / min-40mL / min, and after pretreatment for 0.5h-1h, the mixture is purged with inert gas and cooled to room temperature to obtain a nanodiamond / graphene composite material loaded with platinum ruthenium bimetallic catalyst.

[0016] Application of the nanodiamond / graphene composite material loaded with platinum-ruthenium bimetallic catalyst in CO catalytic oxidation reaction.

[0017] The carrier in the present invention is a nanodiamond / graphene composite material, which is supported by a diamond core. The graphene layer on the surface has abundant defects that can anchor metal species. Pt-Ru is evenly dispersed on the carrier surface in the form of diatomic pairs by bonding with carbon atoms in the graphene defects on the carrier surface.

[0018] The carrier in the present invention is a nanodiamond / graphene composite material, which is supported by a diamond core and has a graphene layer with abundant defects that can anchor metal species. During the impregnation process, Pt and Ru in the solution are respectively [PtCl6] 2- Ru 3+ The presence of two ions with opposite charges facilitates electrostatic attraction, creating the prerequisites for the formation of Pt-Ru atomic pairs. Furthermore, the presence of a small amount of oxygen in the PROX reaction gas used as a pretreatment gas facilitates the uniform distribution of metal atoms on the support surface. Based on these conditions, Pt and Ru atoms form diatomic pairs, bond to carbon atoms in graphene defect sites, and become anchored to the support surface, evenly dispersed across the surface.

[0019] The present invention has the following advantages and beneficial effects:

[0020] (1) The present invention is the first to use a nanodiamond / graphene composite material loaded with a platinum-ruthenium bimetallic catalyst in the CO catalytic oxidation reaction. The catalyst is mainly obtained by loading a metal salt solution containing platinum and ruthenium onto the surface of a nanocarbon material through a co-impregnation method. Ru is used as an additive, and its addition greatly improves the catalytic activity of the catalyst at room temperature, providing a new strategy to improve the CO catalytic oxidation performance of carbon material-loaded Pt catalysts.

[0021] (2) The present invention provides a room temperature preparation method, which makes the Pt-Ru species uniformly dispersed on the surface of the nanocarbon in the form of atomic pairs. Different from pure hydrogen or a mixture of hydrogen and inert gas, a mixed gas of hydrogen, oxygen, helium and carbon monoxide (PROX gas for laboratory use) is used as a pretreatment gas, which helps to achieve the optimization of the Pt-Ru interface site.

[0022] (3) The catalyst provided by the present invention exhibits excellent catalytic performance in the CO oxidation reaction, can achieve a high CO conversion rate at low temperature and can maintain stable performance for a long time.

[0023] (4) The catalyst provided by the present invention has high raw material utilization rate, low cost, simple preparation process, and is easy to promote and apply. BRIEF DESCRIPTION OF THE DRAWINGS

[0024] Figure 1 This is a high-resolution scanning transmission electron microscopy image of the Pt-Ru bimetallic catalyst supported on the nanodiamond / graphene composite material in Example 1.

[0025] Figure 2 This is a high-resolution scanning transmission electron microscopy image of the Pt single-atom catalyst supported on the nanodiamond / graphene composite material in Comparative Example 1.

[0026] Figure 3 This is a high-resolution scanning transmission electron microscopy image of the Ru single-atom catalyst supported on the nanodiamond / graphene composite material in Comparative Example 2.

[0027] Figure 4 The figure is a comparison chart of the CO catalytic oxidation performance of the catalysts prepared in different examples and comparative examples.

[0028] Figure 5 This is a stability curve of the platinum-ruthenium bimetallic catalyst supported by the nanodiamond / graphene composite material in Example 1 at a temperature of 80°C in a reaction atmosphere. DETAILED DESCRIPTION

[0029] During the application of the platinum-ruthenium bimetallic catalyst supported by the nanodiamond / graphene composite material provided by the present invention in the CO catalytic oxidation reaction, the reaction atmosphere consists of CO, O2 and He, wherein the volume ratio of CO to O2 is 1:1.

[0030] In order to make the technical solution of the present invention clearer, the present invention is further described below with reference to the accompanying drawings and embodiments.

[0031] Example 1:

[0032] The preparation process of the catalyst in this embodiment is as follows:

[0033] The detonated nanodiamond powder is subjected to a high-temperature calcination treatment. Due to the grapheneization of the surface, the nanodiamond / graphene composite material powder obtained after calcination is black. The high-temperature calcination process is as follows: the detonated nanodiamond powder is placed in a tubular furnace for calcination, purged with argon at a rate of 100 mL / min, and kept at 1100°C for 4 hours. After the calcination treatment, the nanodiamond / graphene composite material powder can be obtained.

[0034] Take a 25mL small beaker and add 3mL of anhydrous ethanol. Calculate the amount of chloroplatinic acid solution (concentration 20mg / mL) based on the Pt loading of 0.1wt%, and calculate the amount of ruthenium chloride solution (concentration 20mg / mL) based on the Ru loading of 0.05wt%. Use a pipette to measure the required amount of ruthenium chloride solution. Pour the two solutions into the prepared anhydrous ethanol and stir evenly. Weigh 200mg of nanodiamond / graphene composite material powder, add it to the above-mentioned mixed solution, disperse it evenly under ultrasound for 30min, stir it under a magnetic stirrer under open conditions for 20h until the ethanol is completely volatilized, then keep it warm at 60℃ for 12h under vacuum conditions, and cool it to room temperature to obtain a platinum-ruthenium bimetallic catalyst precursor loaded with nanodiamond / graphene composite material. The resulting nanodiamond / graphene composite-supported platinum-ruthenium bimetallic catalyst precursor was then placed in a quartz tube and calcined at 300°C for 1 hour in a mixed atmosphere of 48% H2, 1% CO, and 1% O2 (He balance) at a flow rate of 30 mL / min. After cooling to room temperature in a helium atmosphere at 20 mL / min, the nanodiamond / graphene composite-supported platinum-ruthenium bimetallic catalyst was obtained, which was recorded as 0.1Pt0.05Ru / ND@G.

[0035] The surface morphology of the prepared 0.1Pt0.05Ru / ND@G was analyzed, and the high-resolution scanning transmission electron microscopy images were obtained as shown in the figure. Figure 1 As shown in the figure, it can be seen that Pt atoms and Ru atoms with different brightness contrasts are evenly dispersed on the surface of the carrier, representing that Pt atoms and Ru atoms appear as one bright spot and one dark spot.

[0036] Comparative Example 1:

[0037] The preparation method of this comparative example is the same as that of Example 1, except that Ru is not introduced in this comparative example, and only Pt solution of the same proportion is added to obtain a platinum single-atom metal catalyst supported by a nanodiamond / graphene composite material, which is denoted as 0.1Pt / ND@G. Figure 2 , isolated Pt single atoms (marked by circles) are uniformly dispersed on the surface of the ND@G support without agglomeration.

[0038] Comparative Example 2:

[0039] The preparation method of this comparative example is the same as that of Example 1, except that Pt is not introduced in this comparative example, and only Ru solution of the same proportion is added to obtain a ruthenium single atom metal catalyst supported on a nanodiamond / graphene composite material, which is denoted as 0.05Ru / ND@G. Figure 3 ,It can be seen from the figure that isolated Ru atoms (marked by circles) are evenly dispersed on the surface of ND@G support without agglomeration.

[0040] Comparative Example 3

[0041] The preparation method of this comparative example is the same as that of Example 1, except that the Pt loading amount is 0.1wt% and the Ru loading amount is changed to 0.025%wt, to obtain a platinum-ruthenium bimetallic catalyst supported on a nanodiamond / graphene composite material, which is recorded as 0.1Pt0.025Ru / ND@G.

[0042] Example 2:

[0043] The preparation method of this embodiment is the same as that of Example 1, except that the Pt loading amount is 0.1 wt % and the Ru loading amount is changed to 0.075 wt % to obtain a platinum-ruthenium bimetallic catalyst supported on a nanodiamond / graphene composite material, which is recorded as 0.1Pt0.075Ru / ND@G.

[0044] Example 3:

[0045] The preparation method of this embodiment is the same as that of Example 1, except that the Pt loading amount is 0.1 wt % and the Ru loading amount is changed to 0.1% wt, to obtain a platinum-ruthenium bimetallic catalyst supported on a nanodiamond / graphene composite material, which is recorded as 0.1Pt0.1Ru / ND@G.

[0046] 25 mg of the catalysts prepared in Examples 1 to 3 and Comparative Examples 1 to 3 were weighed and added to a fixed bed reactor, with quartz wool placed at both ends of the reactor. The reaction atmosphere for the activity test was composed of 1% CO + 1% O2 + 98% He (volume ratio), with a reaction gas flow rate of 20 mL / min. The activity of the catalysts was tested in the temperature range of 30-280°C. The test results are shown in FIG. Figure 4As shown in the figure, when the Pt content is fixed and the Ru loading increases from 0 to 0.1wt%, the catalytic performance of the Pt-Ru bimetallic catalyst for CO oxidation first increases and then decreases. When the Ru loading is 0.05%, the performance is the highest, with the highest low-temperature activity and the lowest complete conversion temperature.

[0047] The stability test of the catalyst prepared in Example 1 was conducted as follows: 50 mg of 0.1Pt0.05Ru / ND@G catalyst was weighed and added to a fixed bed reactor. The reaction gas flow rate was 10 mL / min, the atmosphere composition was 1% CO + 1% O2 + 98% He (volume ratio), the reaction temperature was maintained at 80°C, and the sample was tested continuously for 720 minutes. The stability test results are shown in Figure 2. Figure 5 As shown, it can be seen that the catalyst can maintain its activity for a long time without obvious deactivation.

[0048] The above examples are for reference only, but the protection content of the present invention is not limited to the above embodiments. Technical solutions that are similar to the present invention or extended from the concept of this patent are all within the protection scope of the present invention.

Claims

1. A nano-diamond / graphene composite material supported on a platinum-ruthenium bimetallic catalyst, characterized in that: The Pt-Ru elements are uniformly loaded on the graphene layer on the surface of the nanodiamond / graphene composite material in the form of atomic pairs; Wherein Pt is an active component, and its mass percentage is 0.1wt%-0.2wt%; Ru is an auxiliary agent, and its mass percentage is 0.05wt%-0.1wt%; The catalyst is used for CO catalytic oxidation reaction.

2. The nanodiamond / graphene composite material supported platinum-ruthenium bimetallic catalyst according to claim 1, characterized in that: The nano-diamond / graphene composite material is used as a carrier and is a core-shell structure material formed by taking nano-diamond as a core and graphene rich in surface defects as a shell.

3. The method for preparing the nano-diamond / graphene composite material supported platinum-ruthenium bimetallic catalyst according to claim 1 or 2, characterized in that: The steps include: Step 1. Add chloroplatinic acid and ruthenium chloride solution into anhydrous ethanol and mix them evenly to obtain a metal salt solution, load platinum and ruthenium on the nanodiamond / graphene composite material carrier by co-impregnation method to obtain a platinum-ruthenium catalyst precursor supported by the nanodiamond / graphene composite material, and vacuum dry for 12h-24h; Step 2: placing the prepared solid precursor in a quartz tube and pre-treating it in a mixed atmosphere of hydrogen, oxygen, carbon monoxide and helium to obtain the nano-diamond / graphene composite material loaded with platinum-ruthenium bimetallic catalyst.

4. The method for preparing the nano-diamond / graphene composite material supported platinum-ruthenium bimetallic catalyst according to claim 3, characterized in that: In step 1, the nano-diamond / graphene composite material carrier is prepared by high-temperature calcination of nano-diamond powder.

5. The method for preparing the nano-diamond / graphene composite material supported platinum-ruthenium bimetallic catalyst according to claim 4, characterized in that: The high-temperature calcination process is as follows: calcining the nano-diamond powder raw material at 900°C-1100°C for 3h-5h in an inert gas atmosphere and then cooling naturally to graphitize the surface of the nano-diamond powder to obtain a nano-diamond / graphene composite material; Among them, the inert gas flow rate is 80ml / min-100ml / min.

6. The method for preparing the nano-diamond / graphene composite material supported platinum-ruthenium bimetallic catalyst according to claim 3, characterized in that: In step 1, the process of the co-impregnation method is specifically as follows: according to the loading ratio, a chloroplatinic acid solution and a ruthenium chloride solution with a concentration of 20 mg / mL are measured in anhydrous ethanol, and the molar ratio of platinum and ruthenium elements is controlled to be 1:1; a nanodiamond / graphene composite material is added thereto, ultrasonically dispersed evenly, and then stirred with a magnetic stirrer in an open environment. After the ethanol is completely evaporated, it is dried in a vacuum environment and naturally cooled to room temperature to obtain a platinum-ruthenium bimetallic catalyst precursor loaded with a nanodiamond / graphene composite material.

7. The method for preparing the nano-diamond / graphene composite material supported platinum-ruthenium bimetallic catalyst according to claim 6, characterized in that: The ratio of the addition amount of nanodiamond / graphene composite material to anhydrous ethanol is 200:(2-5)mg / mL; the ultrasonic time is 10min-30min, the magnetic stirring time is 12h-24h, the drying temperature is 60°C, and the drying time is 12h-24h.

8. The method for preparing the nano-diamond / graphene composite material supported platinum-ruthenium bimetallic catalyst according to claim 3, characterized in that: In step 2, the mixed atmosphere has the following components by volume ratio: H2 48%, CO 1%, O2 1%, and the balance is He.

9. The method for preparing the nano-diamond / graphene composite material supported platinum-ruthenium bimetallic catalyst according to claim 3, characterized in that: In step 2, during the pretreatment process, the pretreatment temperature is 300°C, the flow rate of the mixed atmosphere is 20mL / min-40mL / min, the pretreatment time is 0.5h-1h, and after pretreatment, the temperature is purged with inert gas to cool to room temperature to obtain a platinum-ruthenium bimetallic catalyst supported on a nanodiamond / graphene composite material.

10. Use of the nanodiamond / graphene composite material supported on a platinum-ruthenium bimetallic catalyst according to claim 1 or 2 in a CO catalytic oxidation reaction.